The Complement System: A Potential Therapeutic Target in Liver Cancer - Meng Yuan; Li Liu; Chenlin Wang; Yan Zhang; Jiandong Zhang (Life, 2022)
Liver cancer is the sixth most common cancer and the fourth most fatal cancer in the world. Immunotherapy has already achieved modest results in the treatment of liver cancer. Meanwhile, the novel and optimal combinatorial strategies need further research. The complement system, which consists of mediators, receptors, cofactors and regulators, acts as the connection between innate and adaptive immunity. Recent studies demonstrate that complement system can influence tumor progression by regulating the tumor microenvironment, tumor cells, and cancer stem cells in liver cancer. Our review concentrates on the potential role of the complement system in cancer treatment, which is a promising strategy for killing tumor cells by the activation of complement components. Conclusions: Our review demonstrates that complement components and regulators might function as biomarkers and therapeutic targets for liver cancer diagnosis and treatment.